Erythropoietin-driven signalling and cell migration mediated by polyADP-ribosylation - Inbar, D (Nature Publishing Group, 2012)
BACKGROUND: Recombinant human erythropoietin (EPO) is the leading biotechnology engineered hormone for treatment of anaemia associated with chronic conditions including kidney failure and cancer. The finding of EPO receptors on cancer cells has raised the concern that in addition to its action in erythropoiesis, EPO may promote tumour cell growth. We questioned whether EPO-induced signalling and consequent malignant cell manifestation is mediated by polyADP-ribosylation. METHODS: Erythropoietin-mediated PARP (polyADP-ribose polymerase-1) activation, gene expression and core histone H4 acetylation were examined in UT7 cells, using western blot analysis, RT–PCR and immunofluorescence. Erythropoietin-driven migration of the human breast epithelial cell line MDA-MB-435 was determined by the scratch assay and in migration chambers. RESULTS: We have found that EPO treatment induced PARP activation. Moreover, EPO-driven c-fos and Egr-1 gene expression as well as histone H4 acetylation were mediated via polyADP-ribosylation. Erythropoietin-induced cell migration was blocked by the PARP inhibitor, ABT-888, indicating an essential role for polyADP-ribosylation in this process. CONCLUSIONS: We have identified a novel pathway by which EPO-induced gene expression and breast cancer cell migration are regulated by polyADP-ribosylation. This study introduces new possibilities regarding EPO treatment for cancer-associated anaemia where combining systemic EPO treatment with targeted administration of PARP inhibitors to the tumour may allow safe treatment with EPO, minimising its possible undesirable proliferative effects on the tumour.